A New Freshwater Cyanosiphovirus Harboring Integrase - Zhong, Kevin Xu; Suttle, Curtis A.; Baudoux, Anne-Claire; Derelle, Evelyne; Colombet, Jonathan; Cho, Anna; Caleta, Jessica; Six, Christophe; Jacquet, Stéphan (Frontiers in Microbiology, 2018)
Pelagic cyanobacteria are key players in the functioning of aquatic ecosystems, and their viruses (cyanophages) potentially affect the abundance and composition of cyanobacterial communities. Yet, there are few well-described freshwater cyanophages relative to their marine counterparts, and in general, few cyanosiphoviruses (family Siphoviridae) have been characterized, limiting our understanding of the biology and the ecology of this prominent group of viruses. Here, we characterize S-LBS1, a freshwater siphovirus lytic to a phycoerythrin-rich Synechococcus isolate (Strain TCC793). S-LBS1 has a narrow host range, a burst size of ∼400 and a relatively long infecting step before cell lysis occurs. It has a dsDNA 34,641 bp genome with putative genes for structure, DNA packing, lysis, replication, host interactions, DNA repair and metabolism. S-LBS1 is similar in genome size, genome architecture, and gene content, to previously described marine siphoviruses also infecting PE-rich Synechococcus, e.g., S-CBS1 and S-CBS3. However, unlike other Synechococcus phages, S-LBS1 encodes an integrase, suggesting its ability to establish lysogenic relationships with its host. Sequence recruitment from viral metagenomic data showed that S-LBS1-like viruses are diversely present in a wide range of aquatic environments, emphasizing their potential importance in controlling and structuring Synechococcus populations. A comparative analysis with 16 available sequenced cyanosiphoviruses reveals the absence of core genes within the genomes, suggesting high degree of genetic variability in siphoviruses infecting cyanobacteria. It is likely that cyanosiphoviruses have evolved as distinct evolutionary lineages and that adaptive co-evolution occurred between these viruses and their hosts (i.e., Synechococcus, Prochlorococcus, Nodularia, and Acaryochloris), constituting an important driving force for such phage diversification.